1978
DOI: 10.1002/kin.550100405
|View full text |Cite
|
Sign up to set email alerts
|

Ene reactions of olefins, part II. The addition of ethylene to propylene and to isobutene and the addition of propylene to propylene

Abstract: The pyrolysis of ethylene-propylene and ethylene-isobutene mixtures has been studied in a static system over the temperature range of 682"-754'K and for initial pressures of each olefin of 33-300 torr. The following molecular ene reactions were observed and the rate constants measured: 25f0.3--"8,000f100000/2.3R?Using thermodynamic data, rate constants for the corresponding retro-ene decomposition reactions were calculated and compared to kinetic data reported for similar compounds. Other products were formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
(5 reference statements)
1
6
0
Order By: Relevance
“…The activation energy is calculated to be 33.3 kcal/mol. This is similar to the experimental activation energy of 37 kcal/mol 1 The ene reactions studied theoretically.
2 Two views of the Becke3LYP/6-31G* transition structure for the ene reaction of propene with ethylene.
…”
Section: Resultssupporting
confidence: 76%
“…The activation energy is calculated to be 33.3 kcal/mol. This is similar to the experimental activation energy of 37 kcal/mol 1 The ene reactions studied theoretically.
2 Two views of the Becke3LYP/6-31G* transition structure for the ene reaction of propene with ethylene.
…”
Section: Resultssupporting
confidence: 76%
“…198 The experimental activation energy for this reaction was reported as 37.0 kcal/mol. 35 DFT using the B3LYP functional and 6-31G* basis sets predicts the activation energy for the reaction of propene with ethene to be 33.3 kcal/mol, 198 with a similar value of 31.5 kcal/mol yielded by the MP2 calculations using 6-31G* basis sets. 198 The feasible pathway of the ene reaction (EN-0 in Fig.…”
Section: S413 Ene Reactionmentioning
confidence: 66%
“…Computational results have shown that the reaction mechanism of the ene reaction is concerted, however, the formation of the C-C bond precedes that of the C-H bond. [101][102][103]196 The formation of 1-pentene by thermal pyrolysis of mixtures of propene and ethene is exothermic with the reaction enthalpy of −21.8 kcal/mol at 700 K. 35,197 The computed reaction energy of the ene reaction between propene and ethene is −21.0 kcal/mol with DFT using the B3LYP exchange-correlation functional and 6-31G* basis sets. 198 The MP2 reaction energy using 6-31G* basis sets is −24.5 kcal/mol.…”
Section: S413 Ene Reactionmentioning
confidence: 99%
“…Computational results have shown that the reaction mechanism of the ene reaction is concerted, however, the formation of the C-C bond precedes that of the C-H bond. 182,216,221 The formation of 1-pentene by thermal pyrolysis of mixtures of propene and ethene is exothermic with the reaction enthalpy of 21.8 kcal/mol at 700 K. 232,233 The computed reaction energy of the ene reaction between propene and ethene is 21.0 kcal/mol with DFT using the B3LYP exchange-correlation functional and 6-31G* basis sets. 234 The MP2 reaction energy using 6-31G* basis sets is 24.5 kcal/mol.…”
Section: Ene Reactionmentioning
confidence: 99%